Longitudinal change of metabolite profile and its relation to multiple risk factors for the risk of developing hepatitis B‐related hepatocellular carcinoma. Issue 11 (10th September 2020) - Huang, Bo‐Yuan; Tsai, Min‐Ru; Hsu, Jia‐Kai; Lin, Ching‐Yu; Lin, Chih‐Lin; Hu, Jui‐Ting; Huang, Yi‐Wen; Liu, Chun‐Jen; Wu, Wan‐Jung; Wu, Chih‐Feng; Sung, Feng‐Yu; Chen, Pei‐Jer; et al.
Abstract: Despite considerable knowledge of viral pathogenesis, the pathophysiological changes related to the multifactorial, multistep process of hepatitis B virus (HBV)‐related hepatocellular carcinoma (HCC) development remains unclear. Longitudinal metabolomics study can reveal biological process for disease progression. We performed metabolite profiling with longitudinal prediagnostic plasma samples from two nested case‐control studies of hepatitis B surface antigen carriers participating in ultrasound screening for HCC, one within a government employee cohort (870 samples from 109 HCC cases and 107 controls) and the other within a hospital‐based cohort (266 samples from 63 HCC cases and 114 controls). Of the 34 measured metabolites, tyrosine, isoleucine, and glutamine were consistently associated with HCC. In analyses combining longitudinal data, a high metabolic risk score based on the three amino acids was robustly associated with increased risk of HCC (OR = 3.71, 95% confidence interval: 2.53–5.42), even after adjustment for clinical factors, or when assessed for different times up to ≥8 years before diagnosis. Similar association was observed in an independent, prospective analysis comprising 633 randomly selected individuals of the government employee cohort. More importantly, this metabolite signature was longitudinally influenced by HBV‐infection phase and involved in gradual progression to liver fibrosis and cirrhosis. Furthermore, mediation analysis showed that the score mediated substantial proportions of the associations of key viral factors, insulin resistance, and diabetes status with HCC risk. Our results suggest that an amino‐acid dysregulation metabotype may play a role in HBV‐related HCC development, and may also be linked to common pathways that mediate increased HCC risks.